Distribution of Haemaphysalis longicornis and associated pathogens: analysis of pooled data from a China field survey and global published data - Zhao, Lin; Li, Jie; Cui, Xiaoming; Jia, Na; Wei, Jiate; Xia, Luoyuan; Wang, Haitao; Zhou, Yuhao; Wang, Qian; Liu, Xueyuan; Yin, Chaonan; Pan, Yusheng; et al. (The Lancet. Planetary health, 2020)
Haemaphysalis longicornis, a vector of various pathogens with medical and veterinary importance, is native to eastern Asia, and recently reached the USA as an emerging disease threat. In this study, we aimed to identify the geographical distribution, hosts, and associated pathogens of H longicornis. Data were collected from multiple sources, including a field survey, reference book, literature review, and related websites. The thematic maps showing geographical distribution of H longicornis and associated pathogens were produced by ArcGIS. Hosts of H longicornis and positive rates for H longicornis-associated pathogens were estimated by meta-analysis. Ecological niche modelling was used to predict potential global distribution of H longicornis. H longicornis was found to be present in ten countries, predominantly in eastern Asia, the USA, Australia, and New Zealand. The tick was known to feed on a variety of domestic and wild animals, and humans. At least 30 human pathogens were associated with H longicornis, including seven species of spotted fever group rickettsiae, seven species in the family of Anaplasmataceae, four genospecies in the complex Borrelia burgdorferi sensu lato, two Babesia species, six species of virus, and Francisella, Bartonella, Coxiella, and Toxoplasma, which were mainly reported in eastern Asia. The predictive modelling revealed that H longicornis might affect more extensive regions, including Europe, South America, and Africa, where the tick has never been recorded before. H longicornis is relatively common in the world, and is associated with various human and animal pathogens. Authorities and health-care workers should be aware of the threat of the tick species to public health and veterinary medicine. Surveillance and further investigations should be enhanced globally. National Natural Science Foundation of China and National Key Research and Development Program of China.